Growth factor regulation of growth factor production by multiple gene transfer to chondrocytes. (February 2013) - Shi, Shuiliang; Mercer, Scott; Eckert, George J.; Trippel, Stephen B.
<x xml:space="preserve">Abstract</x> Of the many classes of molecules regulated by growth factors, growth factors themselves are not well investigated. We tested the hypothesis that combinations of endogenous growth factors interactively regulate the production of other growth factors. Growth factors have therapeutic potential for articular cartilage repair, and gene transfer is a promising approach to growth factor delivery. We tested the hypothesis using adult bovine articular chondrocytes treated with combinations of cDNAs encoding insulin-like growth factor I, bone morphogenetic protein-2 and protein-7, transforming growth factor β1, and fibroblast growth factor 2. We found that these growth factor transgenes regulated each other's growth factor production. This regulation ranged from stimulation to inhibition. Regulation by multiple transgenes was not predictable from the regulatory actions of the individual transgenes. Such interactions may be important for the selection of growth factor genes for cell-based therapies, including articular cartilage repair.